Product Development, Product Certification, and Digital Marketing in Increasing Micro Business Development - Artaya, I Putu (Jurnal Ilmu Manajemen Advantage, 2023)
The problem that occurs in this research activity is the process of developing micro businesses using a three variable approach consisting of product development, product certification and digital marketing implementation, especially in the city of Sidoarjo. The total research sample was 114 micro business actors in the culinary sector with various types of food and beverage products. The sample determination method uses the census method or saturated sample. A group of business actors joined by the name Gumin (food and beverage business actors). The process of collecting research data uses Microsoft forms which are shared via the WhatsApp group of micro entrepreneurs. The analysis method used is multiple linear regression analysis, where the aim of this analysis is to find the estimation equation. The use of estimation equations in regression analysis aims to find out how big the role and influence of each independent variable (X) is on the dependent variable (Y). The results obtained through the analysis were that only two independent variables were significant, i.e product development and product certification, while one independent variable, i.e the application of digital marketing, was not significant. Improving the implementation of digital marketing is the main focus of this micro business group so that they can develop their business better in the future, so they can compete with other culinary businesses. The process of implementing digital marketing can be carried out if micro business actors establish partners with similar business actors, thereby creating mutual benefits.